Constructive episodic simulation, flexible recombination, and memory errors. (22nd January 2018) - Schacter, Daniel L.; Carpenter, Alexis C.; Devitt, Aleea; Roberts, Reece P.; Addis, Donna Rose
Abstract: According to Mahr & Csibra (M&C), the view that the constructive nature of episodic memory is related to its role in simulating future events has difficulty explaining why memory is often accurate. We hold this view, but disagree with their conclusion. Here we consider ideas and evidence regarding flexible recombination processes in episodic retrieval that accommodate both accuracy and distortion.